Pengaruh Human Bone Marrow Mesenchymal Stem Cells Terhadap Penyembuhan Luka Bakar Pada Pembentukan Jaringan Granulasi Tikus DM - Dini Nurhasanah; Gusti Revilla; Deddy Saputra (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2024)
Background: Burns with diabetes mellitus conditions can interfere with the wound healing process. Mesenchymal stem cells have been studied to heal burns, one of which originates from the bone marrow Objective: Determine the effect of human bone marrow mesenchymal stem cells on burn wound healing in the formation of granulation tissue DM rats. Methods: Research is experimental research with post-test only control group design. The research subjects were 30 rats divided into two groups, the control group was given NaCl and the treatment group was given hBM-MSCs. Mice were induced by alloxan to cause hyperglycemia, burns were made using a heated plate. Tissue collection was carried out after termination of the experimental animals on the 3rd, 7th, 14th days and then made histological preparations to assess the formation of granulation tissue. Data were analyzed using Two Way Anova Test. Results: Increase in the number of macrophages, fibroblasts and new blood vessels after hBM-MSCs were given. There were no increase on the 14th day neutrophils and 3rd day lymphocytes. Statistical analysis showed a significant increase in the number of lymphocytes, macrophages, fibroblasts and new blood vessels. Conclusion: The is study concludes that human bone marrow mesenchymal stem cells can increase the formation of granulation tissue by increasing macrophages, fibroblasts and new blood vessels in DM rats.